The Contribution of Students Psychological Assesment in Career Decision-Making Self-Efficacy (CDSE-SF) - Sugiharto , D. Y. P.; Sunawan, Sunawan (KnE Social Sciences, 2019)
This quantitative comparative research study examines Career Decision-Making Self-Efﬁcacy Scale — Short Form (CDSE-SF-SF) between students who have taken psychologicalassessmenttestsandwhohavenevertakenapsychologicalassessment test, in junior high school students in Central Java Province. This study also measured the difference in Career Decision-Making Self-Efﬁcacy based on gender and the origin of the residency area. Bandura’s Self-Efﬁcacy Theory functions as a theoretical framework, while sampling uses cluster random sampling to obtain students who have taken psychological assessment tests (N = 167), and those who have never followed (N = 186) students. Data collection was carried out through a direct survey consisting of 25-questions Career Decision-Making Self-Efﬁcacy Scale-Short Form (CDSE-SF-SF). T-test data analysis showed that there were signiﬁcant differences between students who had taken IQ test, aptitude test and interests test with those who had never followed. The results is IQ test (t (353) = 2.744, p>0.05), aptitude test (t (353) = 4.327, p>0.05) and, interest test (t (353) = 4.991, p>0.05). This implies that the factors of individualparticipationinpsychologicalassessmenttestscontributesigniﬁcantlytothe Career Decision-Making Self-Efﬁcacy relationship. On the basis of these ﬁndings, it is recommended that career decision making must be improved in schools using career guidance and counseling strategies by involving other parties, one of which is the use of psychological assessment tests. Keywords: Career decision-making self-efficacy; IQ test; Junior high school; career development.